Parliamentary Oversight of Defense in Nepal: Mandates and Challenges - Khanal, Bharat (NCWA Annual Journal, 2026)
The Constitution of Nepal mandates parliamentary scrutiny of defense budgets, procurement, policy formulation, and accountability mechanisms, significant challenges persist, including weak political will, institutional fragmentation, historical legacies, and capacity gaps. This article examines the evolving role of parliamentary oversight of defense in Nepal following the 2006 democratic transition, which established civilian control over the military under the Constitution of Nepal in 2015. The legislative framework, such as the Nepali Army Act, 2006, emphasizes democratic accountability but lacks effective implementation due to gaps in inter-institutional coordination and a lack of expertise. Parliamentary committees, including the State Affairs and Public Accounts Committees, play critical roles in oversight but face limitations in accessing sensitive military information and enforcing transparency. The study underscores the need for capacity-building programs for legislators, enhanced institutional memory, and a coherent national security policy to strengthen civilian oversight while respecting military professionalism and operational autonomy. By addressing these gaps, Nepal can advance democratic governance in its defense sector, ensuring alignment with constitutional principles and international humanitarian standards.